Pelatihan Menulis Cerpen Bermuatan Budaya Lokal Untuk Siswa SMK Darussalam Karangpucung - Agnes Apryliana; Helmi Seftiani; Dini Nurhayati (Jurnal Pengabdian Masyarakat Nusantara, 2022)
This community service project aims to train students of SMK Darussalam Karangpucung in writing short stories that contain local culture. This project recognizes the challenges students face in writing short stories, including difficulties in generating ideas and a lack of interest and motivation. Traditional teaching methods focus on lectures and analyzing existing stories, leading to a lack of hands-on experience and boredom. The project implements a five-step approach: preparation, pre-activity surveys, material delivery, writing practice, and question and answer sessions. The material presented includes the essence of short stories, their components (intrinsic and extrinsic elements), imagination techniques, writing tips, and the integration of cultural elements. The students enthusiastically participated in a short story writing practice session with the theme "Personal Experience" and blended local culture. Question and answer sessions allow for open discussion and problem-solving, which further increases student engagement. The project successfully achieved its goal, improving students' writing skills and interest in literature. The active participation of students, especially during writing practice, shows a renewed enthusiasm for the subject. The project also highlights the need for ongoing support and follow-up activities to strengthen the skills acquired. The success of this project is further evidenced by the full participation of the 30 target students, the successful completion of the planned curriculum, the students' real understanding of the material, and their high level of enthusiasm throughout the activity. Although time constraints limited the question and answer sessions, students' willingness to ask questions and their ability to generate creative stories during the practice sessions clearly demonstrated the positive impact of the project.